Cross-tissue integration of genetic and epigenetic data offers insight into autism spectrum disorder. Issue 1 (December 2017) - Andrews, Shan; Ellis, Shannon; Bakulski, Kelly; Sheppard, Brooke; Croen, Lisa; Hertz-Picciotto, Irva; Newschaffer, Craig; Feinberg, Andrew; Arking, Dan; Ladd-Acosta, Christine; Fallin, M. Daniele
Abstract Integration of emerging epigenetic information with autism spectrum disorder (ASD) genetic results may elucidate functional insights not possible via either type of information in isolation. Here we use the genotype and DNA methylation (DNAm) data from cord blood and peripheral blood to identify SNPs associated with DNA methylation (meQTL lists). Additionally, we use publicly available fetal brain and lung meQTL lists to assess enrichment of ASD GWAS results for tissue-specific meQTLs. ASD-associated SNPs are enriched for fetal brain (OR = 3.55;P < 0.001) and peripheral blood meQTLs (OR = 1.58;P < 0.001). The CpG targets of ASD meQTLs across cord, blood, and brain tissues are enriched for immune-related pathways, consistent with other expression and DNAm results in ASD, and reveal pathways not implicated by genetic findings. This joint analysis of genotype and DNAm demonstrates the potential of both brain and blood-based DNAm for insights into ASD and psychiatric phenotypes more broadly. "There have been a number of recent epigenetic studies on autism spectrum disorder. Here, the authors integrate genetic and epigenetic data from cord and peripheral blood and also from brain tissues to show the potential of blood-based epigenetic data to provide insights into psychiatric disorders."